If it's not what You are looking for type in the equation solver your own equation and let us solve it.
73=-4(x-2)-3(6x-7)
We move all terms to the left:
73-(-4(x-2)-3(6x-7))=0
We calculate terms in parentheses: -(-4(x-2)-3(6x-7)), so:We get rid of parentheses
-4(x-2)-3(6x-7)
We multiply parentheses
-4x-18x+8+21
We add all the numbers together, and all the variables
-22x+29
Back to the equation:
-(-22x+29)
22x-29+73=0
We add all the numbers together, and all the variables
22x+44=0
We move all terms containing x to the left, all other terms to the right
22x=-44
x=-44/22
x=-2
| 7=13-2r | | 1/18x=0 | | 48=3+5y | | 5x/7+x/4=3 | | 8x²-8x+2=0 | | 39=2x+x | | 4x+2=1+3x | | 7x-3×=-6+10)+5(-3-3x) | | 3x+8(3+6x)=177 | | 3=w/7-2 | | v/5+90=98 | | -x+7=12-2x | | 4x+2x=36 | | 6/x-8+5/x+8=2/x^2-64 | | q/6-2=3 | | p-79=4/4 | | w/3+12=15 | | -3v+6(v+2)=-9 | | (-2x+70)=180 | | 6x+5(4+2x)=100 | | 4x-(3)+(3)X-4=31 | | 7x-80=3x | | 5/8(x-4)=3/4(x+2) | | -24=5(y-2)-3y | | -1/2+5=3/2(2x-1) | | 7b+4-5=14-5b-3b | | 1y=0+2 | | 7b=15-2b | | 1/6(x+18)-1/2(x-2)=x+6 | | 81=9(s+2) | | 4x-(1)+(10)X-4=31 | | 7=10-3p |